Multiple applications of mepiquat chloride enhanced development of plant‐wide fruits from square initiation to boll opening in cotton. Issue 4 (17th May 2021) - Liao, Baopeng; Ren, Xiaoming; Du, Mingwei; Eneji, A. Egrinya; Tian, Xiaoli; Li, Zhaohu
Abstract: Mepiquat chloride (MC) has been widely used for the field management of cotton ( Gossypium hirsutum L.) and could enhance yield and quality. However, it is not completely clear how MC influences cotton development. A field study was conducted during 2011∼2012 cotton growing seasons to determine the effects of multiple MC applications (from the late seedling stage to near cutout) on the development of each fruit by calendar days and thermal time. Two cotton cultivars (GX3 and XK4) were used for the study. The MC application significantly hastened the appearance of squares across fruiting positions by 0.4–2.9 d in 2011; and those on upper (from the 11th) fruiting branches and on inner (first two) fruiting nodes of middle (5th‐10th) fruiting branches under MC treatment formed 1.8–3.8 d earlier in 2012 compared with control. Also, MC decreased the duration from squaring to flowering by 0.1–0.3 d, and that from bloom to boll opening by 0.9–2.1 d. The MC application reduced the growing degree days (GDD) of most fruiting positions from planting to squaring owing to the early onset of squares. However, it increased the GDD of cotton bolls on the upper fruiting branches during maturation period, presumably due to their early set which exposed them to the higher temperatures during development. These results have improved our understanding of MC‐induced earliness in cotton and could help growers to optimize earliness management. Core Ideas: Maturation of cotton bolls was affected by light and temperature complementation. Multiple mepiquat chloride applications promote the development of cotton fruits plant wide. Multiple MC applications hastened cotton boll maturation without sacrificing boll weight.